Croatia Public Finance Review : Restructuring Spending for Stability and Growth - World Bank (2015)
The Croatia poverty rate, as measured by the international line of moderate poverty at dollar 5 in public-private partnership (PPP) terms, is estimated at 2.8 percent for 2012. The share of the population at risk of poverty, based on a higher national and relative poverty line, also declined substantially prior to the 2008 global financial crisis, although has subsequently increased markedly. The global financial crisis, with the loss of credit, has exposed Croatia's macroeconomic vulnerabilities. This report shows that without addressing macroeconomic weaknesses, through sustained fiscal adjustment and institutional reforms, Croatia will not be able to reignite higher growth and benefit fully from European Union (EU) membership, and the quest for future prosperity may prove elusive. Similarly, without accelerating structural reforms, especially in the area of labor market, investment climate, and public sector efficiency, Croatia will face further stifled competitiveness and any prospects for recovery of growth and jobs. Focusing on the fiscal and public sector related deficiencies, this report systematically analyzes three interrelated issues to assist the Croatian government in informing public policy, strengthening macroeconomic stability, and laying the foundation for a robust recovery: first, it analyzes Croatia's major fiscal weaknesses, risks, and alternative fiscal scenarios, and on that basis, calculates the required fiscal adjustment needed over the medium term. Second, it analyzes the institutional weaknesses and requirements for the efficient use of EU funds in the coming years. Third, the report analyzes the structure of Croatia's public finances and provides a blueprint of the fiscal adjustment of around 5 percentage points of gross domestic product (GDP) over the medium term.